Index of biotic integrity based on fish assemblages for pampean streams and its implementation along the Del Azul stream (Buenos Aires province, Argentina) - Masson, Ignacio (2021)
Aim: Freshwater communities respond to abiotic and biotic changes in the environment, and are widely used as indicators of environmental integrity. Fish have been one of the most used biological groups for this purpose. The Del Azul stream located in the pampean region of Argentina has been monitored using a physicochemical approach with this monitoring being sporadic due to economic and operational constraints associated with the chemical analyses. In this paper we developed an Index of Biotic Integrity for the Del Azul stream (IBIA) based on Karr´s Index of Biotic Integrity as an alternative. Methods: We computed two existent physicochemical indexes for comparison, one of them is the NSF-WQI and the other one is a local index referred to as Water Quality Index for Del Azul Stream and based on the former. Results: The three indexes followed similar trends along the examined reaches, showing good conditions in the upper basin, poor conditions just downstream of the urban area and a recovery state further downstream in the basin. Conclusions: Since the IBIA followed the same patterns as the physicochemical indexes, has a lower implementation cost and it is simpler to apply, we promote it as an alternative to the traditional physicochemical water quality monitoring for pampean streams.